Functionalized Cellulose for Water Purification, Antimicrobial Applications, and Sensors. (23rd April 2018) - Bethke, Kevin; Palantöken, Sinem; Andrei, Virgil; Roß, Marcel; Raghuwanshi, Vikram Singh; Kettemann, Frieder; Greis, Kim; Ingber, Tjark T. K.; Stückrath, Julius B.; Valiyaveettil, Suresh; Rademann, Klaus
Abstract: As the most abundant natural polymer, cellulose presents a unique advantage for large‐scale applications. To fully unlock its potential, the introduction of desired functional groups onto the cellulose backbone is required, which can be realized by either chemical bonding or physical surface interactions. This review gives an overview of the chemistry behind the state‐of‐the‐art functionalization methods (e.g., oxidation, esterification, grafting) for cellulose in its various forms, from nanocrystals to bacterial cellulose. The existing and foreseeable applications of the obtained products are presented in detail, spanning from water purification and antibacterial action, to sensing, energy harvesting, and catalysis. A special emphasis is put on the interactions of functionalized cellulose with heavy metals, focusing on copper as a prime example. For the latter, its toxicity can either have a harmful influence on aquatic life, or it can be conveniently employed for microbial disinfection. The reader is further introduced to recent sensing technologies based on functionalized cellulose, which are becoming crucial for the near future especially with the emergence of the internet of things. By revealing the potential of water filters and conductive clothing for mass implementation, the near future of cellulose‐based technologies is also discussed. Abstract : An overview on the synthesis and applications of functionalized cellulose reveals the role of functionalization methods (e.g., oxidation; esterification; grafting; conductive nanoparticle, carbon, or polymer composite formation) on its physical properties. Existing and foreseeable applications are presented in detail, spanning from heavy‐metal water purification and antibacterial action, to sensing, energy harvesting, and catalysis.